Amplicon-based metagenomics to study the effect of coir age and wood biochar on microbiome in relation to strawberry yield - Xu, Xiangming; Deakin, Greg; Zhao, Jingchen; Passey, Tom; Papp-Rupar, Matevz (Frontiers in Agronomy, 2024)
In the UK, strawberry is mostly grown in coconut coir-substrate under protection. Coir substrate is usually used only for one or two cropping seasons, because continuous reuse of coir without any treatment leads to yield decline. In this study we investigated the changes in bacterial and fungal communities in strawberry roots and bulk coir in relation to: (i) the coir substrate age (cropping seasons), and (ii) oak or beech biochar amendment at planting. Coir age did not affect fungal/bacterial alpha (within-sample) diversity but affected beta (between-sample) diversity.Amendment with either oak or beech biochar did not lead to significant changes in either alpha or beta diversity for both fungi and bacteria, but it did alter the relative abundance of 13 fungal ASVs .This study identified 6 bacterial and 20 fungal ASVs with significant positive linear relationship with coir age and also 8 bacterial and 22 fungal ASVs with significant negative linear relationship with coir age. Notably, the observed strawberry yield decline in reused coir substrate could be associated with a generalist root pathogen, Ilyonectria destructans (ex. Cylindrocarpon destructans), of which the abundance increased annually by 18% an 66% in strawberry root and bulk coir, respectively. Future research is needed to confirm the role of I. destructans in reused coir on strawberry plant health and fruit productivity, and then to identify management strategies for yield decline mitigation.